Online privacy policies : do they really protect consumers' privacy? - Damayanti Iman Abadi (2008)
Privacy concerns have often been considered as barriers to the growth of e-commerce. To help consumers alleviate their privacy concerns, companies post online privacy policies on websites. However, the presence alone does not imply that a website provides protection to consumers’ privacy. The foremost interest in this study is to examine whether online companies, through privacy policies posted on their websites, really protect consumers’ privacy in the course of data handling practices. Content analyses of 50 Singaporean and 50 of Australian websites were undertaken within this study. The findings revealed that although most of the online privacy policies have some elements of data privacy, the level of comprehensiveness was inconsistent and a great number of ambiguities were found. Online privacy policies can alleviate Internet users’ privacy concerns only if users read them. Do they read them? A survey of over 100 Internet users was conducted to gauge their attitude toward online privacy policies. Many Internet users did not read them because online privacy policies were difficult to understand or too long, or because Internet users lacked the time for reading properly. It also showed that a great amount of Internet users being indifference toward online privacy policies.